Epstein-Barr virus directed screening for nasopharyngeal carcinoma in individuals with positive family history: A systematic review. (October 2022) - Chow, James C.H.; Lee, Anne W.M.; Wong, Charlene H.L.; Ng, Wai Tong; Liu, Zhiwei; Tay, Joshua K.; Loh, Kwok Seng; Pace-Asciak, Pia; Cohen, Oded; Corry, June; Rodrigo, Juan Pablo; Tsang, Raymond K.Y.; et al.
Highlights: The systematic review summarizes the role of EBV-directed familial NPC screening. Ten cross-sectional studies (n = 7436) and three cohort studies (n = 4306) were included. EBV positivity rates were high in family members of NPC patients. Family members of NPC patients who are EBV-positive had high risks of developing NPC. Familial NPC screening with EBV serology may be warranted in endemic areas. Abstract: Objectives: Evidence to support Epstein-Barr virus (EBV)-directed population nasopharyngeal carcinoma (NPC) screening has been growing. Familial aggregation is a well-recognized phenomenon in endemic regions. This systematic review summarizes the role of EBV-directed screening in individuals with a positive family history (FH+) of NPC. Methods: We searched four electronic databases from their inception to October 2021. We included studies on individuals with FH+ of NPC who had undergone EBV-directed investigations, with no restriction in the testing methods or analytic techniques. The primary and secondary outcomes were EBV positivity rates and NPC incidence rates, respectively. Meta-analyses were performed using the random-effect model. Results: Ten cross-sectional studies (n = 7436) and three cohort studies (n = 4306) were included. The pooled relative risk (RR) of EBV positivity between individuals with and without FH+ of NPC were 2.79 (95 % CI 1.37–5.68, p = 0.005) for viral capsid antigen (VCA) IgA, 3.09 (95 % CI 0.65–14.83, p = 0.16) for Epstein-Barr nuclear antigen (EBNA1) IgA, and 1.76 (95 % CI 1.04–2.96, p = 0.03) for combined EBNA1/VCA IgA. In the three cohort studies, the NPC incidence rates ranged from 90.2 to 266 per 100 000 person-years with high proportions of early-stage diseases. FH+ individuals who were EBV-positive had a 2.5 to 30.7-fold risk of NPC development compared to their EBV-negative counterparts. Conclusion: Family members of NPC patients had significantly higher EBV positivity rates than the general population. FH+ individuals who are EBV-positive had high risks of developing NPC. Familial screening using EBV serology may facilitate early NPC detection in endemic areas.